Agave-Laurate-Bioconjugated Fructans Decrease Hyperinsulinemia and Insulin Resistance, Whilst Increasing IL-10 in Rats with Metabolic Syndrome Induced by a High-Fat Diet - Angélica Sofía González-Garibay; Georgina Sandoval; Omar Ricardo Torres-González; Blanca Estela Bastidas-Ramírez; Iván Moisés Sánchez-Hernández; Eduardo Padilla-Camberos (MDPI AG, 2024)
Metabolic syndrome (MetS) comprises a cluster of metabolic risk factors, which include obesity, hypertriglyceridemia, high blood pressure, and insulin resistance. The purpose of this study was to evaluate the effects of laurate-bioconjugated fructans on pro- and anti-inflammatory cytokines in Wistar rats with MetS induced by a high-fat diet. Laurate-bioconjugated fructans were synthesized with agave fructans, immobilized lipase B, and vinyl laureate as the acylant. Groups were fed a standard diet (NORMAL), a high-fat diet (HFD), or a high-fat diet plus laurate-bioconjugated fructans (FL PREV) for 9 weeks. A fourth group received a high-fat diet for 6 weeks, followed by simultaneous exposure to a high-fat diet and laurate-bioconjugated fructans for 3 additional weeks (FL REV). The dose of laurate-bioconjugated fructans was 130 mg/kg. Laurate-bioconjugated fructans reduced food and energy intake, body weight, body mass index, abdominal circumference, adipose tissue, adipocyte area, serum triglycerides, insulin, insulin resistance, and C-reactive protein but they increased IL-10 protein serum levels and mRNA expression. The impact of laurate-bioconjugated fructans on zoometric and metabolic parameters supports their potential as therapeutic agents to improve obesity, obesity comorbidities, insulin resistance, type 2 diabetes mellitus, and MetS.